Simple fabrication of colloidal crystal structural color films with good mechanical stability and high hydrophobicity. (December 2015) - Meng, Yao; Tang, Bingtao; Xiu, Jinghai; Zheng, Xixi; Ma, Wei; Ju, Benzhi; Zhang, Shufen
Abstract: Weak mechanical stability and low hydrophobicity have been considered as major obstacles for actual applications of structural color films from colloidal crystals. This paper presents these films with good mechanical properties and high hydrophobicity by employing a simple preparation strategy. With this strategy, the mechanical property of the structural color films was remarkably improved by the structure lock effect of polyacrylate adhesive when its latex was used as a co-assembly component with polystyrene microspheres. Likewise, the hydrophobicity of structural color films was enhanced by using cationic surfactant. Furthermore, the obtained films exhibited several unique characteristics, such as good mechanical stability, high hydrophobicity, and bright structural color. Therefore, the combination of hydrophobicity and mechanical stability was significant for potential architectural applications of paint and external decoration. Graphical abstract: Highlights: Good mechanical stability was improved by the lock effect of polyacrylate adhesive. The high hydrophobicity was realized by absorbing long carbon chain. The materials are cheap and the preparation process is simple. The PS/PA photonic crystal films have bright structural color.